Radiology of equine cheek teeth and sinus disorders. Issue 9 (10th October 2014) - Barakzai, Safia
Abstract : Radiography remains the first‐line diagnostic tool for evaluation of the equine cheek teeth and sinuses, despite more advanced imaging modalities such as CT and scintigraphy becoming widely available. The introduction of computed and direct digital radiography has undoubtedly resulted in improved image quality, as compared to traditional film techniques. Familiarity with correct radiographic techniques is probably the single most important factor in being able to obtain good‐quality images and correctly interpret equine skull radiographs. This article considers radiographic abnormalities associated with common disorders affecting the equine sinuses and cheek teeth.